河北省高素质人才资源开发研究 = Study of high quality human resources development in Hebei province of China - 王淑玲 Wang, Shu Ling (2008)
The essay is to achieve the objective of building up the micro and macro mechanism of high quality human resources development. Guided by human resources and motivation theories, the essay adopts the qualitative, quantitative and systematic research method to address the issue of Hebei province's human resource development on the basis of mass statistical data.